2015
DOI: 10.16929/as/2015.763.68
|View full text |Cite
|
Sign up to set email alerts
|

Quelques propriétés des estimateurs à noyaux gamma pour des échantillons de petites tailles

Abstract: Abstract. In this paper, we study the nonunit mass of the gamma (gamma and the modified gamma) kernels estimator for the finite samples. For this, we propose to use the normalization approach (Macro-normalization and the Micro-Normalization) to correct the problem of the nonunit mass. In the aim to illustrate the necessity of the normalization approach a detailed simulation study investigates the local and global performances of the considered estimators. The obtained results show the good performances of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The aim of this part is to carry out a comparison study of the performances of the normalized gamma kernel estimators, proposed in the paper of Cherfaoui et al (2015), with those obtained with other boundary correction approaches. To do this, we consider the same examples, the same approaches and the same steps simulation treated in Zhang (2010), namely:…”
Section: Comparative Study Between the Boundary Correction Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of this part is to carry out a comparison study of the performances of the normalized gamma kernel estimators, proposed in the paper of Cherfaoui et al (2015), with those obtained with other boundary correction approaches. To do this, we consider the same examples, the same approaches and the same steps simulation treated in Zhang (2010), namely:…”
Section: Comparative Study Between the Boundary Correction Methodsmentioning
confidence: 99%
“…For densities not satisfying the shoulder condition, the author has shown that the gamma kernel estimator has a severe boundary problem and its performance is inferior to that of the boundary kernel estimator. Recently, Cherfaoui et al (2015) were interested in the properties of gamma kernel estimators for finite samples. By simulation studies, the authors analyzed some proprieties of the gamma kernel density estimators for the different variants of the gamma kernel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this proposition, one can note that for non-classical kernels, the total mass Λ(n, h, K) = Λ n of f n is positive and fails to be equal to 1 in general see, e.g., Cherfaoui et al (2015). Table 5 permit to observe that Λ n ∈ [0.9, 1.1].…”
Section: Propertiesmentioning
confidence: 98%